2006
DOI: 10.1109/tsp.2006.879282
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of reflectance spectra using robust nonnegative matrix factorization

Abstract: Abstract-In this correspondence, we present a robust statistics-based nonnegative matrix factorization (RNMF) approach to recover the measurements in reflectance spectroscopy. The proposed algorithm is based on the minimization of a robust cost function and yields two equations updated alternatively. Unlike other linear representations, such as principal component analysis, the RNMF technique is resistant to outliers and generates nonnegative-basis functions, which balance the logical attractiveness of measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…(Guillamet et al, 2001) have suggested the use of a diagonal weight matrix Q in a new factorization model, AQ ≈ WHQ, in an attempt to compensate for feature redundancy in the columns of W. This problem can also be alleviated using column stochastic constraints on H . Other approaches that propose alternative cost function formulations include but are not limited to (Hamza and Brady, 2006;Dhillon and Sra, 2005). A theoretical analysis of nonnegative matrix factorization of symmetric matrices can be found in (Catral et al, 2004).…”
Section: Numerical Approaches For Nmfmentioning
confidence: 99%
“…(Guillamet et al, 2001) have suggested the use of a diagonal weight matrix Q in a new factorization model, AQ ≈ WHQ, in an attempt to compensate for feature redundancy in the columns of W. This problem can also be alleviated using column stochastic constraints on H . Other approaches that propose alternative cost function formulations include but are not limited to (Hamza and Brady, 2006;Dhillon and Sra, 2005). A theoretical analysis of nonnegative matrix factorization of symmetric matrices can be found in (Catral et al, 2004).…”
Section: Numerical Approaches For Nmfmentioning
confidence: 99%
“…(8) reduces to the weighted NMF presented in Eq. (12). A local minimum can be found by the following update rules…”
Section: A the Half-quadratic Minimizationmentioning
confidence: 99%
“…Recently, some variants have been proposed to improve the robustness of original NMF. The L 1 −L 2 function in [12] was used for the purpose of robust factorization. The optimization problem is solved by a general gradient descent scheme, which is computational expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it has already found diverse applications in data spectral analysis, mostly as a tool for blind unmixing or extraction of pure spectra (endmembers) from observed noisy mixtures. Examples include Raman scattering (e.g., Sajda et al, 2003;Li et al, 2007;Miron et al, 2011), hyperspectra unmixing (e.g., Miao and Qi, 2007;Zymnis et al, 2007;Zhang et al, 2008;Jia and Qian, 2009;Guo et al, 2009;Huck et al, 2010;Chan et al, 2011;Heylen et al, 2011;Qian et al, 2011;Iordache et al, 2011;2012;Plaza et al, 2012;Bioucas-Dias et al, 2012;Zdunek, 2012), spectral unmixing in microscopy (e.g., Pengo et al, 2010), chemical shift imaging (e.g., Sajda et al, 2004), reflectance spectroscopy (e.g., Pauca et al, 2006;Hamza and Brady, 2006), fluorescence spectroscopy (e.g., Gobinet et al, 2004), two-photon spectroscopic analysis (e.g., Hancewicz and Wang, 2005), astrophysical ice spectra unmixing (e.g., Igual et al, 2006;Igual and Llinares, 2008;Llinares et al, 2010), and gas chromatography-mass spectrometry (e.g., Likic, 2009). …”
Section: Introductionmentioning
confidence: 99%